High prevalence of mutations in perilipin 1 in patients with precocious acute coronary syndrome. (January 2020) - Bonello-Palot, Nathalie; Laine, Marc; Cuisset, Thomas; Ronchard, Thibault; Desgrouas, Camille; Merono, Françoise; Ibrahim-Kosta, Manal; Cerino, Mathieu; Blanchard, Arnaud; Bourgeois, Patrice; Levy, Nicolas; Loundou, Anderson; et al.
Abstract: Background and aims: Genetic partial lipodystrophies are rare heterogeneous disorders characterized by abnormalities of fat distribution and associated metabolic complications including a predisposition for atherosclerotic cardiovascular disease. We hypothesized that the milder forms of these diseases might be underdiagnosed and might result in early acute coronary syndrome (ACS) as the first sign of the pathology. Methods: We performed targeted sequencing on a panel of 8 genes involved in genetic lipodystrophy for 62 patients with premature ACS, and selected heterozygous missense variations with low frequency. To confirm those results, we analyzed a second independent group of 60 additional patients through Sanger sequencing, and compared to a control group of 120 healthy patients. Results: In the first cohort, only PLIN1 exhibited variants in more than 1 patient. In PLIN1, 3 different variants were found in 6 patients. We then analyzed PLIN1 sequence in the second cohort with premature ACS and found 2 other patients. Altogether, 8 patients were carriers of 4 different mutations in PLIN1 . The variant frequencies in the total cohort of 122 patients were compared to frequencies observed in a local control cohort and in 2 different public databases showing a significant difference between patient vs control group frequencies for two mutations out of 4 (c.245C > T p = 10 −4 ; c.839G > A p = 0.014). Discussion: This is the first study that identifies a high frequency of potential pathogenic mutations in PLIN1 related to early onset ACS. These findings could contribute to the prevention and care of precocious ACS in families carrying those mutations. Graphical abstract: Image 1 Highlights: High throughput sequencing revealed mutations in PLIN1 in patients with premature acute coronary syndrome (ACS). Two mutations in PLIN1 close to phosphorylation sites are strongly correlated to precocious ACS. We observed no correlation between the presence of a mutation and a recurrent event of ACS.